N '-Benzoyl-N,N-diethylthiourea: a monoclinic polymorph - Ligia R Gomes (2010)
In the crystal of the title compound, C(12)H(16)N(2)OS, inversion dimers linked by pairs of N-H center dot center dot center dot S hydrogen bonds occur, generating R(2)(2)(8) loops. The molecules are also linked by weak C-H center dot center dot center dot O hydrogen bonds. The structure is isostructural with that of N'-benzoyl-N,N-diethylselenourea [Bruce et al. (2007). New J. Chem. 31, 1647-1653].